1999
DOI: 10.1017/s1047951100007344
|View full text |Cite
|
Sign up to set email alerts
|

Palliative balloon valvoplasty of the pulmonary valve in tetralogy of Fallot

Abstract: Balloon dilation of the pulmonary valve was performed in 54 patients with tetralogy of Fallot with severe cyanosis, high haematocrit and severe valvar pulmonary stenosis. Clinical, echocardiographic, angiographic, and haemodynamic data were analyzed before and after the procedure. After balloon dilation, the systemic oxygen saturation increased from a mean value of 66% to 85%. The mean value of the haematocrit before dilation was 55 + 13, and decreased to 47 after dilation (p < 0.002) in 2 months follow-up. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
3
4
0
1
Order By: Relevance
“…Like many of the earlier series,[1922] we observed significant growth of the branch pulmonary arteries and pulmonary annulus following BPV. Growth can be explained by the symmetric increase in antegrade flow after BPV.…”
Section: Discussionsupporting
confidence: 86%
“…Like many of the earlier series,[1922] we observed significant growth of the branch pulmonary arteries and pulmonary annulus following BPV. Growth can be explained by the symmetric increase in antegrade flow after BPV.…”
Section: Discussionsupporting
confidence: 86%
“…Sluymans and colleagues, 14 however, were able to demonstrate significant growth of the pulmonary valve, and also a reduced requirement for transannular patching. Both Heusch et al, 12 and Massoud and colleagues, 11 were able to demonstrate growth of the major pulmonary arteries, and that has been a more consistent finding in previous reports. Improved flow, and hence equal growth of both pulmonary arteries, should be a further potential advantage of balloon dilation, since surgical shunts tend to favour the ipsilateral pulmonary artery.…”
supporting
confidence: 76%
“…11 " 13 It was hoped that the increased flow following dilation would stimulate growth of the pulmonary valve. It is disappointing, therefore, that of the three current papers, only Massoud et al 11 are able to support this contention. Sluymans and colleagues, 14 however, were able to demonstrate significant growth of the pulmonary valve, and also a reduced requirement for transannular patching.…”
mentioning
confidence: 93%
“…Some studies related the size of the pulmonary annulus to the aorta, but this is less well validated. Several investigators described improved growth of the annulus by 2 SD or more, [40][41][42][43][44][45][46] and Kreutzer et al 47 found that z increased from −4.0 to −3.3.…”
Section: Balloon Dilatation and Stentingmentioning
confidence: 99%